Three-dimensional Medical Printing and Associated Legal Issues in Plastic Surgery: A Scoping Review. Issue 4 (27th April 2023) - Knoedler, Leonard; Knoedler, Samuel; Kauke-Navarro, Martin; Knoedler, Christoph; Hoefer, Simon; Baecher, Helena; Gassner, Ulrich M.; Machens, Hans-Guenther; Prantl, Lukas; Panayi, Adriana C.
Abstract : Summary: Three-dimensional printing (3DP) represents an emerging field of surgery. 3DP can facilitate the plastic surgeon's workflow, including preoperative planning, intraoperative assistance, and postoperative follow-up. The broad clinical application spectrum stands in contrast to the paucity of research on the legal framework of 3DP. This imbalance poses a potential risk for medical malpractice lawsuits. To address this knowledge gap, we aimed to summarize the current body of legal literature on medical 3DP in the US legal system. By combining the promising clinical use of 3DP with its current legal regulations, plastic surgeons can enhance patient safety and outcomes.